A Preliminary Survey of the Postacute Symptoms of COVID-19 among Hospital-Discharged Patients and a Proposed Quantitative Framework for Assessment - Dutta, Abhijit; Mitra, Subhasis; Mitra, Dalia (Journal of Health and Allied Sciences NU, 2022)
Background Following a massive outbreak of the coronavirus disease 2019 (COVID-19) pandemic, a significant number of survivors are still suffering from residual symptoms and complications. We designed a preliminary study to evaluate such symptom spectra in COVID-19 patients who had been discharged from the hospital.Methods A telephone interview was conducted with 100-randomly chosen hospital-discharged COVID-19 survivors from the electronic patient record. The interview structure and method were developed by a panel of experts. A specially trained group conducted the interviews and data collection. The statistical analysis was performed in accordance with the data type (continuous and categorical). Group comparisons were also done between intensive care unit (ICU) versus general ward admission, and patients discharged between 3 and 12 weeks versus more than 12 weeks. Additionally, world clouds were used for better visualization of various prevalent symptoms.Results Eighty-two participants were finally included for interview after preliminary screening. Fifty-three patients (64.6%) were male participants; 74.4% had at least one symptom. In general, fatigue, cough, insomnia, and shortness of breath were the most common persistent symptoms. Symptoms were more prevalent among the patients discharged from ICU compared with those discharged from the general ward. Cough, loss of appetite, depression, and incoherence were more common in patients after 12 weeks of hospital discharge.Conclusion There is a wide range of persistent symptoms in the COVID-19 survivors who have been discharged from the hospital. Some symptoms arise or persisted even after 12 weeks. Based on the study results, available literature, and expert consensus, an assessment form has been developed that could be used for further research and clinical assessment of similar problems. Large-scale epidemiological study (longitudinal and cross-sectional) is needed to understand the nature and prevalence of the postacute phase of COVID-19 at the country level. The results of this study could inform the stakeholders and policymakers for taking necessary steps toward a further decision.
Keywords: COVID-19; long haulers; postacute COVID-19; persistent COVID-19 Symptoms; post-COVID-19 manifestations; post-COVID-19 syndrome